LncRNA of peripheral blood mononuclear cells: HYMAI acts as a potential diagnostic and therapeutic biomarker for female major depressive disorder - Bu, Tianyi; Yang, Jiarun; Zhou, Jiawei; Liu, Yeran; Qiao, Kexin; Wang, Yan; Zhang, Jili; Zhao, Erying; Owura, Boakye Kwame; Qiu, Xiaohui; Qiao, Zhengxue; Yang, Yanjie (Frontiers in Psychiatry, 2025)
IntroductionAs a common and complex mental disorder, major depressive disorder (MDD) has brought a huge burden and challenges globally. Although the incidence of female MDD is twice that of male MDD, there are still no accurate diagnostic and treatment criteria for female MDD. The potential of long non-coding RNAs (lncRNAs) as efficient and accurate diagnostic and therapeutic biomarkers provides more possibilities for early and accurate diagnosis of MDD.MethodsFirst, the differential expression profile of lncRNAs in peripheral blood mononuclear cells (PBMCs) between MDD patients and healthy controls was established based on high-throughput sequencing analysis. Then, the potential biomarker was screened out by quantifying differentially expressed lncRNAs based on quantitative real-time PCR. To further investigate the function of biomarkers in the pathogenesis of MDD, bioinformatics analysis on downstream target genes was carried out.ResultsThe expression profile screened out 300 differentially expressed lncRNAs. HYMAI was proved to be the potential diagnostic biomarker. Its expression levels were significantly higher in MDD patients than in healthy controls with high potential diagnostic value. Based on bioinformatics analysis, a HYMAI–miRNA–mRNA network and a protein–protein interaction network were established, which also showed that HYMAI is closely related to MDD.DiscussionOur findings showed that the dysregulated expression of lncRNA HYMAI may be the pathophysiological basis of women suffering from MDD. Here, insight into the molecular mechanism of women’s susceptibility to MDD is shown. Meanwhile, a new perspective for future female MDD prevention, diagnosis and treatment, evaluation, detection, and intervention is provided.